The impact of osteotomy technique for corticotomy-assisted orthodontic treatment (CAOT) on oral health-related quality of life - Cassetta, M; Di Carlo, S; Giansanti, M; Pompa, V; Pompa, G; Barbato, E (European review for medical and pharmacological sciences, 2012)
Corticotomy in accelerating orthodontic tooth movement, also defined as corticotomy-assisted orthodontic treatment (CAOT), is a promising technique that recently had many applications in orthodontics. The purpose of this study was to compare the use of piezoelectric surgery and conventional rotatory osteotomy technique for CAOT, determining the duration of surgery and oral health-related quality of life (OHRQoL). CAOT was performed in a sample of subjects, randomly choosing piezoelectric surgery (PS Group) or conventional rotary osteotomy technique (RT Group). The duration of surgery was recorded and the oral health-related quality of life evaluated using the short form Oral Health Impact Profile (OHIP-14) preoperatively, 3 and 7 days after surgery. t-test and Cronbach's alpha were used for statistical analysis. 12 patients (mean age 14; range: 13-17) were enrolled. The time needed to complete the osteotomy cuts was greater (p = 0.1) for the piezoelectric surgery group (mean 34.3 minutes; range 35.3-32.6) than for the rotator group(mean 28.2 minutes; range 27.1-29.2). Oral health-related quality of life deteriorated from baseline (OHIP-14 mean: 6.33) to first follow-up, 3 day after surgery, in both groups (PS Group: 22.67 OHIP-14; RT Group: 21.33 OHIP-14). At 7 days follow-up there was a nearly complete recovery of the original OHIP-14 values , even faster with the conventional rotary osteotomy technique; however, no statistically significant differences were recorded between the two methods (p = 0.35). Cronbach's alpha values indicated an excellent internal consistency reliability. In clinical decision-making regarding the use of corticotomy-assisted orthodontic treatment, it should be aware of the expected decrease in oral health-related quality of life both using piezoelectric surgery or rotary osteotomy technique. In addition, the piezoelectric osteotomy requires a longer surgical time.